Analysis and heading control of continuum planar snake robot based on kinematics and a general solution thereof. (3rd March 2016) - Ariizumi, Ryo; Tanaka, Motoyasu; Matsuno, Fumitoshi
Abstract : This paper presents a kinematic calculation and control method for an inextensible continuum planar snake robot. The snake robot is assumed to move without side slipping; this constraint makes it easy to construct its kinematic model based on which we can analyze the movement of the robot. The kinematic model is expressed as a semi-linear partial differential equation (PDE). We discuss the general solution of the PDE and a calculation method based on it. However, the constraint also raises the problem of singular posture. The problem of singularities has been addressed for a snake robot with a serial link structure; however, for a continuum snake robot, much less research has been carried out. In this paper, we propose a method for controlling the direction of movement while avoiding singularities. The validity of our method is tested through simulations and experiments. Graphical Abstract: